Konstruktywizm i pedagogika różnorodności w kontekście edukacji włączającej - Jolanta Rzeźnicka-Krupa (Problemy Wczesnej Edukacji)
Constructivism is a very complex and ambiguous concept, whereas the constructivist approach is mostly presented in three main aspects: ontological and epistemological (conditions and capabilities of reality existence and cognition), psychological (mental processes of knowledge constructing) and pedagogical (processes of learning and creating concepts). In this article I am searching the answer to two basic questions, the first one reading: What are the potential results of the constructivist approach in connection with diversity pedagogy and inclusion learning for education and the functioning of schools? The posthuman critique of social constructivism formulates the second of the questions I want to answer in the text: how can the constructivist approach cooperate with some new contemporary social theories, especially the new realism (materialism) and pedagogy of things? Employing the Piagetian concept of decentration, I take a critical look at how and in what sense constructivism could influence the change of meanings ascribed to categories like norm(s), learning difficulties or special educational needs, as well as reformulate the general philosophy of education and eventually affect the functioning of schools as accessible learning environments.